2019
DOI: 10.12688/f1000research.16402.1
|View full text |Cite
|
Sign up to set email alerts
|

Pore timing: the evolutionary origins of the nucleus and nuclear pore complex

Abstract: The name “eukaryote” is derived from Greek, meaning “true kernel”, and describes the domain of organisms whose cells have a nucleus. The nucleus is thus the defining feature of eukaryotes and distinguishes them from prokaryotes (Archaea and Bacteria), whose cells lack nuclei. Despite this, we discuss the intriguing possibility that organisms on the path from the first eukaryotic common ancestor to the last common ancestor of all eukaryotes did not possess a nucleus at all—at least not in a form we would recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 60 publications
5
47
0
Order By: Relevance
“…In general, many of the nucleoporin sequences have diverged from the lower eukaryotes to the higher ones. 7,10 Similar to the conserved architectural features, we observed that the biochemical behavior of CTC complexes is also comparable (Figures 2-5). In case of the rat CTC complexes, it has been observed that these complexes, at higher concentration, can form higher order oligomers, with diverse stoichiometric combinations.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In general, many of the nucleoporin sequences have diverged from the lower eukaryotes to the higher ones. 7,10 Similar to the conserved architectural features, we observed that the biochemical behavior of CTC complexes is also comparable (Figures 2-5). In case of the rat CTC complexes, it has been observed that these complexes, at higher concentration, can form higher order oligomers, with diverse stoichiometric combinations.…”
Section: Discussionsupporting
confidence: 73%
“…8,9 Additionally, considerable evidence suggests that many nucleoporins are evolutionary divergent. 7,10 Three of the Nups (Nup62, Nup54, and Nup58), are known to form the central transport channel (CTC). Among them, Nup62 appears to be conserved across various species.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear pores are large macromolecular complexes consisting of approximately 30 different nucleoporins (NUPs) (each present in multiple copies) that are embedded in the nuclear envelope (Field and Rout, 2019. NPCs act as essential gateways for molecular transport into and out of the nucleus and play additional crucial roles in the regulation of gene expression and genome organization 77,78 . In malaria parasites, nuclear pores have hardly been studied and only six NUPs have so far been identified 79-83 , of which four have been localized in P. falciparum asexual blood stage parasites [PfNUP116 (PF3D7_1473700) 80 , PfNUP221/PfNUP100 (PF3D7_0905100) 83 , PfNUP313 (PF3D7_1446500) 79 , PfSEC13 (PF3D7_1230700) 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our finding of NLS-type sequences in the ribosomal proteins uS12, uL3, uL15, and uL18 suggests that at least some cellular proteins evolved NLS-motifs long before the nucleus emerged, indicating that the initial function of NLSs could have been distinct from directing protein transport. Why the NLS-motifs emerged in ribosomal proteins in the Archaea -in species that have neither cell nucleus nor karyopherin proteins to recognize the NLS-type motifs -remains unclear 30,31 , as does what advantage might have been conferred by having these signals in the absence of nuclear-cytoplasmic transport. Furthermore, the initial function of NLS-type sequences in cells in the absence of the nuclear envelope and the nuclear-cytoplasmic trafficking system is unknown.…”
Section: Discussionmentioning
confidence: 99%